From the pathogenesis of chronic cerebral ischemia to targeted therapy - D. V. Zakharov; Yu. V. Yarygina; V. A. Mikhailov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2024)
Chronic progressive cerebrovascular pathology is a powerful disabling factor in modern society. Chronic cerebral ischemia is based on microcirculation and neuroinflammation problems, which are mutually potentiating pathogenetic aspects. As a search for modern pathogenetically oriented targeted therapy, great attention is paid to cerebral capillary disease, oxidative stress in brain tissue and the issues of suppressing neuroinflammation. The article presents the materials of experimental and clinical studies of Ginkgo biloba extract and choline, as well as their combination — Choline Strong®